Women Victims of Sexual Violence: How Does Indonesian Criminal Law Responsibility for Psychological Trauma? - Rhesas Shalatan; Mega Fitri Hertini (WISE Pendidikan Indonesia, 2026)
Sexual violence is a health problem affecting women and adolescents throughout the world, and the phenomenon is particularly prevalent in Indonesia. Sexual violence not only causes physical harm, but also psychological trauma that has long-term impacts on the mental, emotional, and social lives the victims. This study aims to examine psychological trauma from the perspective of Indonesian criminal law, and to analyze Indonesian criminal law responsibility toward the psychological trauma experienced by victims. This study adopts a normative-juridical research method with statute and conceptual approaches, which are then analyzed qualitatively through descriptive-analytical and prescriptive techniques with reference to Law No. 23 of 2004 on the Elimination of Domestic Violence, Law No. 31 of 2014 on the Protection of Witnesses and Victims, and Law No. 12 of 2022 on Sexual Violence Crimes. The findings show that Indonesian criminal law view psychological trauma as an inner wound like a physical injury, and therefore it must be compensated and restored. Indonesian criminal law responsibility for victims’ psychological trauma is channeled through preventive, curative, restitutive, and reintegrative dimensions oriented toward victim recovery. However, its implementation still faces several obstacles, including the dominance of a retributive approach, limited acces to psychological recovery services in regional areas, and lack a of understanding among law enforcement officers regarding victims’ trauma.